Cosmology: What One Needs to Know - Albright, John R. (Zygon, 2000)
Cosmology, the study of the universe, has a past, which is reviewed here. The standard model—the Big Bang, or the hot, dense early universe that is still expanding—is based on observations that are basically consistent but which require additional input to improve the agreement. Out of the early universe came the galaxies and stars that shine today. The future of the universe depends on the density of matter: too much mass leads to the Big Crunch; too little leads to eternal expans ion and cooling. The dark-matter problem prevents us from knowing which will be the fate of the universe. Thelimits of what may be called “scientific” are addressed.